Cities database - Hanson, J (University of Oxford, 2017)
These data were originally assembled for a D.Phil. at the University of Oxford, which has now been published as a monograph. If you would like to cite this material, please refer to my book: Hanson, J. W., (2016), An Urban Geography of the Roman World, 100 B.C. to A.D. 300, (Oxford: Archaeopress). More information about how urbanism was defined, how the catalogue was compiled, how the size of the inhabited area of each site was measured, and other details can be found in the same work. These data are not intended to be final and reflect the state of knowledge in the field in 2016.